The Effect of Project-Based Learning on Improving Students' Speaking Ability on Procedure Text - Khairiyah, Siti Fadhillah; Prawati, Atni; Aruan, Rumiri (TELL - US JOURNAL, 2025)
This study focuses on particular teaching strategies that are thought to enhance students' speaking abilities. Project-Based Learning is a suitable and relevant teaching approach for all educational levels. Its main concept is to link students' experiences with their school environment and encourage them to gain new knowledge. The aim of this study is to determine whether Project-Based Learning is an effective teaching method for improving students' speaking abilities, specifically on procedure text. The subject of this study was students in class x c of SMA Pembangunan in Bagan Batu. This study was pre-experimental research by using one group pretest-posttest design. Furthermore, the data was collected through speaking test. The finding showed that mean score in pretest was 54.76 while in posttest was 73.43. It means that there was a significant improvement on the students’ speaking ability on procedure text. The aspects which are improved including students’ vocabulary, pronunciation, grammar, fluency, and comprehension. To conclude, Project-Based Learning helps students to develop their self-confidence in speaking English and it can make teaching speaking become more interesting.